Mechanism study for metastasis-related drug resistance of breast cancer cells - Yu, Jing Yi (2015)
Three breast cancer cell lines have been generated from MDA-MB-231 cells in Prof. Kathy Qian Luo’s Lab, including 231-C3, 231-M1 and 231-M1A cells. These cell lines are of increasing metastatic potential and were treated with H2O2, UV light, doxorubicin and docetaxel, which are of different potential in generation of reactive oxygen species (ROS). Among them UV light and doxorubicin are both ROS generators. H2O2 is a ROS, whereas docetaxel is one chemotherapy medication known to be of limited ROS generation potential. Experimental results with doxorubicin, H2O2 and UV irradiation showed that the more metastatic 231-M1A and 231-M1 cells display less chemosensitivity compared to the less metastatic 231-C3 cells. Experiment with docetaxel, on the other hand, did not show the above differential result. Therefore, enhanced resistance to oxidative stress should be a possible mechanism for the strong metastatic potential for breast cancer cells. Proteomics method was used to study the underlying mechanisms and search for molecular signatures for antioxidant ability of 231-M1 and 231-M1A cells. Two key proteins, glutathione S-transferase omega-1 (GTO1) and glutathione S-transferase P (GSTP1) were identified, which are found to be involved in cellular oxidative stress response and up-regulated in 231-M1 and 231-M1A cells. Therefore, they may be two of molecular regulators providing metastatic breast cancer cells enhanced antioxidant ability.